The Effect of Problem Based Learning Worksheet on Critical Thinking Skills of Eight Grade Students: A Perspective from Gender Difference - Ardiansyah, Angga; Mulyati*, Yayuk; Wicaksono, Azizul Ghofar Candra (Universitas Syiah Kuala, 2024)
Critical thinking skills (CTS) are essential in the 4.0 era. However, the attempts to enhance these skills during learning are still suboptimal, particularly in science education at the junior high school. Gender is believed as one affecting factor on students critical thinking. The research investigated the effects of problem based learning (PBL) student worksheets on students critical thinking from the perspective of gender differences. This quasy experimental research applied pretest-posttest nonequivalent multiple group design. The samples were chosen through purposive sampling, resulting in one male class having 24 students and one female class having 24 students. The research instruments included a lesson plan, a PBL-based student worksheet, and pretest-posttest questions that had been validated. Data analysis uses statistical tests in the form of paired and independent sample t-tests, and N-gain. The analysis indicated that using PBL-based student worksheets increases CTS more effectively in female students than in male students. These are proven by paired and independent sample t-tests showing a significant difference (Sig. 2-tailed = 0.000 0.050) with N-gain signifies a moderate increase of 0.6 for male students and a high increase of 0.7 for female students. These findings may serve as recommendations to enhance students critical thinking and as a reference for gender-segregated schools in designing learning programs that optimize the role of each gender